Why Are Not-For-Profit Hospitals in the US So Much More Profitable Than For-Profit Hospitals? - Christopher Mouré; Shai Gorsky (Capital as Power - Toward a New Cosmology of Capitalism, 2023)
When it comes to social institutions, not-for-profit organizations (NFPs) allegedly strike a balance between the private and public realm. While privately owned and operated, not-for-profits are distinguished by their ostensibly public purpose – in eschewing private profits, they claim to make the pursuit of some social benefit their primary objective. However, not all not-for-profits are equal. While most make little or no revenue, let alone net income, some NFPs collect billions in revenue and hundreds of millions in net income.
Keywords: P1; I1; 330; differential accumulation; hospitals; profits; United States